Kebijakan Otomotif di Indonesia 1966-1996: Memahami Konteks Politik Proses Lahirnya Kebijakan Publik - Erwan Agus Purwanto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1997)
Automotive industrialization is the most relevant topic for discus to understand the development of industrialization in Indonesia. Because, automotive industry has specific character as representation of Indonesian strategy that is sensitive influenced by political factors. Many interests and missions have to accommodate in automotive industry have made automotive industry become dynamic and uncertain sector to be influenced. This research intended to understand the dynamic changing of automotive policies among 1966-1996, that are contains many controversial policies, with policy study approach. This approach does to answer the research question: how political contect will affect policy making process in Indonesian automotive policies. The research analysis focused on the understanding of factors interaction in policy making process by observing the patterns of the interaction among the government, business man, political and economical enviroment. Based on the research result, political context of automotive policies among period 1966-1996 was influenced by strong patronage in the Indonesian automotive policy making process because the interest in: nativism, foreign capital pressure, and nepotism.